УВЕЛИЧЕНИЕ НАГРУЗКИ НА ЭЛЕКТРОПРИВОД ПРИ ДЕЙСТВИИ ГИРОСКОПИЧЕСКОГО МОМЕНТА - Антонов, А.Е.; Киреев, В.Г.; Петухов, И.С. (Інститут електродинаміки НАН України, Київ, 2016)
The mechanism of the load on the drive motor, when changing its position in space is considered. As shown, the source of the load is the gyroscopic moment, the action of which the resistance increases in the rotor bearings. The dependence of the load torque from the kinetic moment of the rotor and from the rotor angular velocity of its rotation is obtained. It was found that for devices with active compensation of the gyroscopic moment mainly in the choice of drive power there is time to operation. References 5, figures 5, table 1.